Protective Effect of Keluoxin against Diabetic Nephropathy in Type 2 Diabetic Mellitus Models. (19th October 2021) - Yang, Xiaomei; Han, Xuke; Wen, Qing; Qiu, Xianliang; Deng, Huan; Chen, Qiu
Abstract : Diabetic nephropathy (DN) is a chronic kidney disease that develops in patients with diabetes mellitus (DM). Renal dysfunction and persistent proteinuria are the main clinical features of DN. Podocyte injury is an important cause of persistent proteinuria and diabetic kidney disease (DKD) progression. Traditional Chinese patent medicines can improve renal function by enhancing autophagy and promoting apoptosis. Keluoxin is a Chinese patent medicine that has the effect of invigorating qi and nourishing yin, activating blood, and eliminating blood stasis. Therefore, we hypothesized that Keluoxin may have a protective effect against diabetic nephropathy in rats with type 2 DM. Rats induced with diabetes through streptozocin (STZ) injection and a high-fat and high-sugar diet were treated with Keluoxin (0.63 g/kg/day) for 8 weeks, and renal function, biochemical indicators, and histopathological changes in renal tissues were observed. Immunofluorescence staining and western blot analysis were used to detect the expression of autophagy-related proteins. The results showed that Keluoxin reduced blood glucose and lipid levels, improved renal function, and alleviated renal histopathological changes in rats with DN. The therapeutic effect was similar to that of Irbesartan (15.6 mg/kg/day). It is inferred that the mechanism works through reducing the obstruction of downstream pathways of autophagy by improving the lysosomal degradation function and alleviating podocyte injury. This study demonstrates that Keluoxin could regulate autophagy in podocytes, alleviate kidney injury in rats with DN, and have a protective effect on renal function; its mechanism can thus be a potential therapy for DN.